Real‐life effectiveness of first‐line anticancer treatments in stage IIIB/IV NSCLC patients: Data from the Czech TULUNG Registry. Issue 11 (5th October 2020) - Brat, Kristian; Bratova, Monika; Skrickova, Jana; Barinova, Magda; Hurdalkova, Karolina; Pesek, Milos; Havel, Libor; Koubkova, Leona; Hrnciarik, Michal; Krejci, Jana; Fischer, Ondrej; Zemanova, Milada; et al.
Abstract : Background: Data regarding real‐life effectiveness of any treatment may improve clinical decision‐making. The aim of this study was to evaluate real‐life effectiveness of tyrosin‐kinase inhibitors, bevacizumab and pemetrexed as first‐line treatments in patients with advanced/metastatic non‐small cell lung cancer (NSCLC). Methods: We analyzed data of 2157 patients of the Czech TULUNG Registry of patients with advanced/metastatic NSCLC who received modern‐era treatments between 2011 and 2018. Patients treated with gefitinib, erlotinib, afatinib, bevacizumab (+ maintenance), pemetrexed (+ maintenance) as first‐line therapy were included in the study. A systematic literature search separately identified clinical trials suitable for calculation of comparator pooled OS and PFS for each regimen. For each subgroup, basic characteristics and survival data (Kaplan‐Meier estimates) are shown. We propose the "index of real‐life effectiveness" (IRE), a ratio of real‐life OS/PFS and comparator pooled OS/PFS. Univariate and multivariate logistic regression identified factors were associated with longer OS (ie, IRE>1.1). Results: Survival analysis showed median OS of 23 months for erlotinib, 29.3 months for afatinib, 19.6 months for gefitinib, 12.2 months for pemetrexed, 17.5 months for pemetrexed maintenance, 15.8 months for bevacizumab and 15.8 months for bevacizumab maintenance. Calculated IREs for OS for the regimens were: erlotinib 1.013, afatinib 1.184, gefitinib 0.736, pemetrexed 1.188, pemetrexed maintenance 1.294, bevacizumab 1.178, and bevacizumab maintenance 1.189. Multivariate regression analysis showed that these factors were associated with longer OS: lower PS for afatinib; lower PS, absence of adverse events and female sex for bevacizumab; and lower PS and female sex for pemetrexed. Conclusions: This study clearly demonstrated that real‐life effectiveness of certain treatment regimens may strongly differ in various populations/health care systems, and comparison between TULUNG data and pooled survival data from trials showed higher real‐life effectiveness for most of the studied first‐line regimens. Lower ECOG PS, younger age, female sex and adverse events were associated with longer survival in most regimens. Key points: Significant findings of the study: Comparison between TULUNG data and pooled survival data from trials showed higher real‐life effectiveness for most of the studied first‐line regimens; for most regimens, lower ECOG PS, younger age, female sex and adverse events were associated with longer survival. What this study adds: Real‐life effectiveness of certain treatment regimens may strongly differ in various populations/health care systems. Abstract : Comparison between our TULUNG data and pooled survival data from clinical trials showed higher real‐life effectiveness for most of the studied first‐line regimens. We found that lower ECOG PS, younger age, female sex and adverse events were associated with longer survival. We demonstrated that real‐life effectiveness of certain treatments may strongly differ in various populations and health care systems.